Modelagem, construção, testes e análise de desempenho de um gerador a relutância chaveado - Silveira, Augusto Fleury Veloso da (2008)
The switched reluctance generator emerged as an alternative generator and grew in interest among the scientific community during the last decade. It has a simple construction and comes up as a competitive option when one deals with variable speed applications and also when power electronics is required. Nowadays the most aimed applications are the aircraft applications, hybrid or electric vehicles and wind power. This machine has a doubly salient structure without copper in the rotor. The coils are concentrated in the stator poles. Thus, there is low copper and iron consumption and, because of it, this machine is closer to the modern environmental requirements. The switched reluctance generator driving uses power electronics and needs continuous information about the rotor position to drive properly the switches of the phases. The optimal design for this machine is still been established from the experimental results. Many operational details are under investigation. The machine has two different electrical circuits: one for the excitation and other when the load is fed. It is possible to insulate those two circuits and because of this it is also possible to reduce the electronic switches count. This work is helpful to understand how the SRG works. To get it the goals were to build a mathematical model for this machine and to simulate its operation. And than to know how it dynamically conducts. A prototype was constructed and used to test some driving circuits with it. Also it is presented an extensive comparative study. With this all this work presents a contribution for the development of this kind of machinery.